Standardising accessibility: Transferring knowledge to society - Matamala, Anna; Orero, Pilar (Journal of Audiovisual Translation, 2018)
This article describes standardisation work in the field of media accessibility with a focus on the international standardisation bodies ISO (International Organization for Standardization) and ITU (International Telecommunication Union). It provides an overview of what standards are and how standardisation agencies work, with a focus on the technical procedures, types of documents and Code of Conduct to be followed. The specific tasks of working groups dealing with access services is presented and their main outputs in the form of standards are summarised. The article also discusses the main challenges researchers face when getting involved in standardisation work and the benefits of transferring into society and the industry through standardisation.